Broadcasting Strategy Implementation of Malire Ki Sunda Program as Media Preserving Sundanese Culture at SMTV Sumedang Local Television Station - Putri, Shinta Hartini; Pratami, Tiarani Vidia; Sugiarta, Nugraha (Research Collaboration Community (Rescollacom), 2024)
Malire Ki Sunda is a mandatory program of SMTV Sumedang to provide information about the noble values of the Sundanese Society, and arts that are closely related to Sundanese Culture. The speakers presented were Artists and Cultural Practitioners. The purpose of this study is to determine the broadcasting strategy implementation of Malire Ki Sunda Program as media preserving Sundanese culture at SMTV Sumedang local television station. This research uses the theory of Program Broadcasting Strategy from Peter K. Pringle. The approach used is qualitative with a case study method. Data were obtained from the results of interviews and observations. Data processing and analyzing techniques use Miles and Huberman data analysis model. The results obtained from this study are: First, planning to discuss the determination of themes, concepts, and production funds, the second is production stages which include pre-production, productions, and post-production activities, the third is evaluation and supervision programs by program directors and hosts, and the fourth program is executions to determine the broadcast time and promotion of the program. The main factor behind SMTV Sumedang use of this broadcasting strategy is globalization, SMTV Sumedang is a local television that has a cultural preservation program, namely Malire Ki Sunda, Regional Regulation No. 1 of 2020 concerning Sumedang Puseur Sundanese Culture, and the youth do not comprehend about Sundanese culture.